2020
DOI: 10.1186/s12891-020-03484-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between pelvic obliquity and scoliosis, hip displacement and asymmetric hip abduction in children with cerebral palsy: a cross-sectional registry study

Abstract: Background: Pelvic obliquity (PO) is common in individuals with cerebral palsy (CP). The prevalence of PO in a population of children with CP and its associations with scoliosis, hip displacement and asymmetric range of hip abduction were analysed. Methods: Over a 5-year period all pelvic radiographs from the Swedish surveillance programme for CP and the recorded data for scoliosis and hip abduction in children from southern Sweden at Gross Motor Function Classification System (GMFCS) levels II-V were analysed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
(19 reference statements)
3
9
0
Order By: Relevance
“…A secondary analysis of the factors determining the apex side of scoliosis demonstrated that PO was a significant factor; however, handedness or asymmetric upper limb function had no significant effect on the direction of scoliosis. The current results were consistent with the previous reports that 89% of the patients with CP had the convexity of scoliosis on the opposite side of the high side of the PO [ 5 ]. We additionally found that this tendency was offset in the case of patient whose secondary curve was at the lumbar level.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A secondary analysis of the factors determining the apex side of scoliosis demonstrated that PO was a significant factor; however, handedness or asymmetric upper limb function had no significant effect on the direction of scoliosis. The current results were consistent with the previous reports that 89% of the patients with CP had the convexity of scoliosis on the opposite side of the high side of the PO [ 5 ]. We additionally found that this tendency was offset in the case of patient whose secondary curve was at the lumbar level.…”
Section: Discussionsupporting
confidence: 93%
“…Previous researchers have investigated the association between coronal spine deformities and PO in scoliosis [ 5 , 19 ]. Biomechanically, the pelvis serves as an important pivot between the trunk and lower extremities, playing a fundamental role in maintaining an unsupported sitting posture and ambulation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hips were grouped into categories according to the MP: < 33% MP, 34%-50% MP, 51%-100% MP, and > 100% MP. 14 Pelvic obliquity, an established proxy for sitting balance, was measured on each radiograph while the patient was supine with legs straight, in the middle of the table, using the method described by Hägglund and his colleagues 31,32 preoperatively, postoperatively when out of brace or hip spica, and at final follow-up radiograph, prior to any further intervention.…”
Section: Methodsmentioning
confidence: 99%
“…A prior study of 127 patients with degenerative scoliosis established that 91% had PO, though no definition of PO was provided. Additional sources have proposed thresholds of 3 degrees, 11 5 degrees, 12 15 degrees, 10 or 1 cm to define PO, 1 each citing different literature to support their threshold.…”
mentioning
confidence: 99%